2022
DOI: 10.1038/s41467-022-31806-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient use of cement and concrete to reduce reliance on supply-side technologies for net-zero emissions

Abstract: Decarbonization strategies for the cement and concrete sector have relied heavily on supply-side technologies, including carbon capture and storage (CCS), masking opportunities for demand-side intervention. Here we show that cross-cutting strategies involving both the supply and demand sides can achieve net-zero emissions by 2050 across the entire Japanese cement and concrete cycle without resorting to mass deployment of CCS. Our analysis shows that a series of mitigation efforts on the supply side can reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(35 citation statements)
references
References 47 publications
0
35
0
Order By: Relevance
“…In this study, we confirmed that the CU indicators are highly inconsistent with CF in the material-producing and product-manufacturing industries, while RP is highly inconsistent with CF in the services industry. Understanding the interlinkage of both material and carbon flows in these industries , should thus be an important prerequisite to any discussion of reduction measures. In particular, the Scope 3 category showed marked conflict between improving MFIs and CF improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed that the CU indicators are highly inconsistent with CF in the material-producing and product-manufacturing industries, while RP is highly inconsistent with CF in the services industry. Understanding the interlinkage of both material and carbon flows in these industries , should thus be an important prerequisite to any discussion of reduction measures. In particular, the Scope 3 category showed marked conflict between improving MFIs and CF improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Key to this strategy is how to deal with products with stringent impurity requirements . There is already evidence that upcycling is possible with today’s technologies through product design changes, advanced sorting, alternative shredding, processing, and component manipulation. , Low-carbon concrete : Thermal and electric energy efficiency will improve to 3 GJ/t-clinker and 85 kWh/t-cement, respectively, while the emission intensity of fuel will drop to 89 kg-CO 2 /MJ . The clinker-to-cement ratio will be reduced from the current 83% to the global average of 72%, while the cement content of concrete will be reduced by 15% .…”
Section: Methodsmentioning
confidence: 99%
“…Based on a lifecycle evaluation that included the supply sector [50], Kua et al (Singapore) examined climate change mitigation through food and plastic waste recovery and estimated a 37% reduction compared to the status quo scenario, which focuses on incineration. In a recent study in Japan, Watari et al [51] quantitatively proposed a pathway to carbon neutrality in the Japanese cement and concrete sector based on both supply-and demand-side measures. One of the primary issues to be addressed in the future is the presentation of the GHG emission reduction effects of material cycle measures, including such demand-side behavioral changes, and their reflection in future scenarios.…”
Section: Potential Reduction By More Materials Cycles and Resource Ef...mentioning
confidence: 99%